Dietary and genetic factors affecting the cholesteryl ester transfer protein and lipoprotein metabolism - Noone, Enda (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2001)
The cholesteryl ester transfer protein (CETP) plays an inherent role in the redistribution of neutral lipids between high density lipoproteins (HDL) and very low density lipoproteins (VLDL) and low density lipoproteins (LDL). This is an important step in the process of reverse cholesterol transport. The activities of CETP may possibly be atherogenic as CETP activity transfers CE from HDL to VLDL and LDL with the reciprocal transfer of triglyceride (TAG). The consequence of CETP activity is increased LDL and VLDL cholesterol concentrations, and increased HDL TAG and reduced HDL cholesterol concentrations. This is a lipoprotein profile which is associated with an increased in risk for the development of CAD.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin